Fluoxetine-Induced Dyskinesia in a Pediatric Patient: A Case Report and Literature Review on Implications of Polypharmacy and Serotonergic Regulation - Mehmet Ayhan Cöngöloğlu; Şahin Bodur; Esra Doğan Elmas; Cansel Azizağaoğlu (Düzce Tıp Fakültesi Dergisi)
Movement disorders associated with psychiatric medications are primarily related to the side effects of dopamine receptor-blocking drugs, which are mostly antipsychotic medications. These side effects are acute dystonic reactions, akathisia, dyskinesia, neuroleptic malignant syndrome, parkinsonism, and various tardive syndromes. Dyskinetic movements are characterized by hyperkinetic, repetitive movements of the extremities, facial, and perioral muscles. In rare cases, dyskinetic movements may occur with the use of selective serotonin reuptake inhibitors (SSRIs) through an indirect D2 blocking mechanism. In this case report, dyskinesia observed after increasing the dose of fluoxetine in a patient using methylphenidate and risperidone was presented. It was thought that the SSRI inhibited dopamine activity through dopamine receptor antagonism and that SSRIs may increase risperidone concentrations by inhibiting CYP450 metabolism. There are few cases reported in the literature regarding SSRI-induced dyskinesia, information is limited on this subject. This case report highlights the potential dyskinesia side effect of SSRIs.